Les universitaires et intellectuels rwandais à l'épreuve du génocide des Tutsi : première mémoire, première histoire - Rémi Korman (Les Cahiers de Framespa)
Based on interviews as well as public and private archives, the author seeks to understand the role of Rwandan academics and intellectuals in the memorialization of the genocide against the Tutsi in Rwanda. The article focuses on three dimensions. First, it examines the early interpretations of the history of the genocide and its consequences on Rwandan society. Secondly, it considers the history of the genocide commissions of inquiry and the patrimonialization of the traces of the genocide. Finally, the article gives an account of the first Rwandan historian studies on the genocide. By restoring the role of often unknown actors, it aims to refocus the debate on the first Rwandan historiography of the genocide.